The Proposed Model TOPSIS – AHP – Kansei Model for Improvement of Learning Courses at University Economic of Ho Chi Minh City - Truong Viet , Phuong; Tran Thi Thu , Ha; Nguyen Tien , Dat (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Evaluating the quality of courses at universities plays an important role in ensuring the quality of education. This work involves understanding students' desires and goals, the problems they are facing, and giving appropriate advice. Course evaluation based on traditional methods will not be applicable to criteria of varying importance. This paper has presented a novel approach using TOPSIS - AHP and Kansei approach which is applied to evaluate courses’ quality. In the proposed model, TOPSIS and AHP techniques in order to evaluate courses, quantified by both qualitative and quantitative factors. Kansei evaluation is applied to quantify the sensibilities of students’ emotions, sensibilities while evaluating courses at universities. In case studies of the University of Economics Ho Chi Minh City, experimental results showed that the proposed model indicates the effectiveness of course evaluation for the improvement of courses through online and offline methods. The authors posit that our proposed approach has the potential to address student feedback engagement issues.
Keywords: Decision support system; TOPSIS – AHP – Kansei; Course evaluation